Integration design of supply chain hybrid simulation - Tan, Wen Jun (2019)
A supply chain (SC) consists of multiple entities representing the retailers, manufacturers, distributors or suppliers. A firm can be one of the entities within the whole SC. To study the external effects on its internal operations, the firm needs to construct a SC model. It may have sufficient data to build a detailed model of its operational processes. However, since it has no control or visibility over the external entities, it is difficult to construct the rest of the SC model at the same level of detail. This paper proposes a hybrid model of the SC using integration design. It allows the whole SC to be captured at the broad view through system dynamics, and the target firm to be represented using agent-based model. The proposed hybrid model is therefore able to capture different behaviors of the same system, e.g, strategic planning of the whole SC, and detailed operational process of individual entities. To demonstrate the applicability of the hybrid model, we evaluate the model through a case study of disruption management policies.